2017
DOI: 10.4103/ijccm.ijccm_419_16
|View full text |Cite
|
Sign up to set email alerts
|

Pain measurement in mechanically ventilated patients with traumatic brain injury: Behavioral pain tools versus analgesia nociception index

Abstract: Introduction:Pain is highly prevalent in critically ill trauma patients, especially those with a traumatic brain injury (TBI). Behavioral pain tools such as the behavioral pain scale (BPS) and critical-care pain observation tool are recommended for sedated noncommunicative patients. Analysis of heart rate variability (HRV) is a noninvasive method to evaluate autonomic nervous system activity. The analgesia nociception index (ANI) device (Physiodoloris®, MDoloris Medical Systems, Loos, France) allows noninvasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
1
12
0
3
Order By: Relevance
“…However, the role of norepinephrine on ANI values in ICU patients is still to be determined, and the quite small number of patients included in the current study may prevent any interpretation of this discrepancy. Indeed, another study has shown decreased median [min-max] ANIi (55 [22-100]) and ANIm (69 [32-100]) during tracheal suctioning with traumatic brain injury, which is similar to the current study [15]. However, no clear difference could be observed without or with epinephrine: median [ Our study presents certain limitations, in particular because of its retrospective design.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the role of norepinephrine on ANI values in ICU patients is still to be determined, and the quite small number of patients included in the current study may prevent any interpretation of this discrepancy. Indeed, another study has shown decreased median [min-max] ANIi (55 [22-100]) and ANIm (69 [32-100]) during tracheal suctioning with traumatic brain injury, which is similar to the current study [15]. However, no clear difference could be observed without or with epinephrine: median [ Our study presents certain limitations, in particular because of its retrospective design.…”
Section: Discussionsupporting
confidence: 83%
“…To date, four studies have reported the use of ANI monitoring in ICU patients [12][13][14][15]. In the first study performed in conscious burn patients, the performance of ANI to detect pain during dressing changes procedures was studied, with an area under the receiver-operating characteristics curve (ROC AUC) of 0.76 [95% CI 0.75-0.76] [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the autonomic nervous system (ANS) is responsible for the regulation of this inflammatory reflex, and its balance is essential to the maintenance of the body's homeostasis [9,10]. A physiological metric for the measurement of the ANS is the analysis of heart rate variability (HRV) and, more specifically, the analgesia nociception index (ANI) monitor has proven to be a crucial tool for the measurement of the ANS and nociception in both surgical and critically ill patients [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…BPS is the second most used pain scale in ICUs. It evaluates three behavioral domains (facial expressions, movement of upper limbs, and compliance with ventilation) 64 and it is valid in different languages 53 , 58 , 64 74 and samples 35 , 75 78 ( Table 1 ). Psychometric properties, as internal consistency (Cronbach α coefficient ranged from 0.63 to 0.72, 65 , 74 , 79 , 80 ) interrater reliability (Kappa coefficient ranged from 0.67–0.83 64 , 79 , 81 and ICC of 0.95, 65 ) sensitivity, specificity, criterion and discriminant validity (significant increases of 2–3 points in BPS scores following nociceptive procedures 64 , 65 , 69 , 74 , 79 , 80 ) were supported previously and confirm the advantages of BPS use, including frequency of pain assessments and patient’s positive outcomes.…”
Section: Pain Assessment In Icusmentioning
confidence: 99%